2019
DOI: 10.1093/toxsci/kfz075
|View full text |Cite
|
Sign up to set email alerts
|

ahr2, But Not ahr1a or ahr1b, Is Required for Craniofacial and Fin Development and TCDD-dependent Cardiotoxicity in Zebrafish

Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor that binds environmental toxicants and regulates gene expression. AHR also regulates developmental processes, like craniofacial development and hematopoiesis, in the absence of environmental exposures. Zebrafish have 3 paralogs of AHR: ahr1a, ahr1b, and ahr2. Adult zebrafish with mutations in ahr2 exhibited craniofacial and fin defects. However, the degree to which ahr1a and ahr1b influence ahr2 signaling and contribute to fin and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 66 publications
(121 reference statements)
1
27
0
Order By: Relevance
“…As discussed earlier, zfAhr2 has been shown to be involved in mediating toxicity of dioxinlike compounds and PAHs, as well as a suggested a role of in the development of the nervous system 43,44,95 . On the other hand, Karchner et al found high expression levels of zfahr1b in zebrafish embryos compared to the other two zfahrs, suggesting a role of zfAhr1b in embryonic development 24 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…As discussed earlier, zfAhr2 has been shown to be involved in mediating toxicity of dioxinlike compounds and PAHs, as well as a suggested a role of in the development of the nervous system 43,44,95 . On the other hand, Karchner et al found high expression levels of zfahr1b in zebrafish embryos compared to the other two zfahrs, suggesting a role of zfAhr1b in embryonic development 24 .…”
Section: Discussionmentioning
confidence: 94%
“…Toxic responses to TCDD, PCB126 and B[a]P in zebrafish and mummichog have been demonstrated to be mediated by Ahr2 [37][38][39][40][41][42][43][44][45]88 . Other studies also suggested a role of Ahr2 in mediating TCDD toxicity in red seabream, medaka, and Atlantic salmon 30,33,89 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We focus on the AhR2 clade, since the receptors of this clade mediate the effects of PHAHs and PAHs in fish [ 18 , 19 , 45 , 46 ]. The AhR2 isoforms were shown to play a key role in the developmental and cardiovascular toxicity of dioxin-like chemicals in several fish species including rainbow trout, and they contribute to the developmental toxicity of PAHs [ 45 , 47 , 48 ]. Beyond, there exists evidence that AhR2 signaling is involved in the toxic effects of HAHs and PAHs on the reproductive system of fish [ 11 , 49 ].…”
Section: Introductionmentioning
confidence: 99%